Myths and misunderstanding concerning the implementation of cooperative learning - Arató, Ferenc (Autonomy and Responsibility Journal of Educational Sciences, 2022)
In the last two decades during the implementation of cooperative learning in the context of Hungarian public education we have faced several myths and misunderstandings about cooperative learning from the perspectuives of teachers and student teachers. In this article we list the most frequent ones and attempt to answer them in the spirit of cooperative learning paradigm. We start with the clarifi cation of the concept of cooperative learning itself and continue with those questions which seem to be barriers of the implementation of cooperative learning in the Hungarian context.